LEVEL OF KNOWLEDGE, ATTITUDE AND BEHAVIOR OF THE COMMUNITY IN BANJAR PANDE AND BANJAR PASEKAN TOWARDS THE ROLE OF WOLBACHIA MOSQUITOES AS A STRATEGY TO CONTROL DENGUE FEVER - I Made Gede Asta Ginawan; I Made Sukada; Romy Muhammad Dary Mufa; Kadek Karang Agustina; I Wayan Masa Tenaya; I Gusti Ngurah Bagus Trilaksana (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Wolbachia is a naturally occurring bacterium found in various insects, such as fruit flies, butterflies, and moths. It has been utilized as an innovative strategy to control the spread of dengue fever by releasing Wolbachia-infected Aedes aegypti mosquitoes. This study aimed to assess the public’s understanding of the benefits of Wolbachia-carrying mosquitoes as a dengue control measure. Data were collected through questionnaire-based interviews with residents of Banjar Pande and Banjar Pasekan in Kaba-Kaba Village, Kediri District, Tabanan Regency. Pre-test results revealed that the level of knowledge among Banjar Pande residents was 50%, attitude 45%, and behavior 66%. Meanwhile, in Banjar Pasekan, pre-test scores for knowledge, attitude, and behavior were 47%, 47%, and 60%, respectively. These findings indicate that, prior to educational interventions, community awareness, attitudes, and behavior regarding Wolbachia mosquitoes as a dengue control strategy were at a moderate level. Post-test results demonstrated significant improvements, with the community exhibiting deeper knowledge, increased concern, and greater acceptance of Wolbachia technology. This study concludes that targeted education effectively enhances public awareness and support for Wolbachia as a sustainable dengue prevention approach.